Corporate venture capital organizations in Germany: a comparison - Christiana Weber; Barbara Weber (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This paper analyzes the goals, the organizational structures and processes, and the investment criteria that underlie venture strategies in Germany today, using a sample of 20 corporate venture capital organizations (CVCs). The performance of these CVCs is examined and the data are compared with those generated by studies on German independent venture capital organizations (VCs) as well as with European and U.S. CVCs. The study concludes that German CVCs focusing either on financial or on strategic objectives are more successful than those with a mixed approach. Further, CVCs with a strong financial focus seem to be financially - and sometimes also strategically - more successful than CVCs with a strong strategic focus. Finally, based on these findings, theses concerning the CVC's organizational learning are developed. – – Anhand von 20 Corporate Venture Capital Gesellschaften (CVCs) in Deutschland analysieren die Autorinnen im vorliegenden Papier deren Ziele, Organisationsstrukturen und -prozesse sowie deren Investitionskriterien. Es wird zum einen der finanzielle und strategische Erfolg dieser CVCs untersucht, zum anderen werden die Ergebnisse mit Daten deutscher klassischer VCs sowie europäischer und U.S. CVCs verglichen. Die Kernaussage der Studie ist, dass deutsche CVCs, die sich entweder auf strategische oder auf finanzielle Ziele konzentrieren, erfolgreicher sind als solche, die beide Ziele gleichermaßen verfolgen. Desweiteren wird deutlich, dass die CVCs mit einem überwiegend finanziellen Ansatz finanziell - und zuweilen auch strategisch - erfolgreicher zu sein scheinen als CVCs mit einem überwiegend strategischen Investitionsfokus. Abschließend werden - auf diesen Ergebnissen basierend - Thesen zum organisationalen Lernverhalten der CVCs entwickelt.
Keywords: 300; Risikokapital; Investmentfonds; Betriebswirtschaftliches Ziel; Erfolgsfaktor; Vergleich; Deutschland